REALITY COUNSELING FOR DRUG PRISONERS IN ADJUSMENT PERIOD IN PRISON - Fadila, Fadila (Corolla International Conference, 2022)
Abstract This study aims to help new inmates, especially inmates who are involved with drug cases, to be able to adapt and be responsible in a new environment, in the Class II A Curup Prison, Rejang Lebong Regency. This study uses a Mix Method approach. The research data used are primary data and secondary data. Primary data was obtained from a questionnaire, while secondary data was obtained from literature studies, internet website searches and also obtained from documentation at the Class II A Curup prison institution. The data analysis technique is by taking measurements, selecting samples using purposive sampling technique, providing reality counseling services, conducting self-evaluation of new inmates after being given counseling, then making conclusions based on the verification of the data obtained. The results of this study showed that out of 10 inmates, 7 people had a low level of adjustment and 3 people had a moderate level of adjustment. The implementation of this reality counseling makes the inmates specifically for drugs smarter in adjusting to the environment they face so that their thinking becomes more rational and their anxiety can be overcome. Based on the results of the analysis, it can be seen that the probability number of Asmyp. Sig.(2-tailed) adjustment of inmates specifically for drugs in prison Class II A is 0.005 or probability below alpha 0.05 (0.005 < 0.05), from these results it can be concluded that the level of adjustment of inmates specifically for drugs in Class II A prisons improved significantly after being given Reality Counseling. Keywords: Reality Counseling, Drug Prisoners, Adjustment